Correction: Genetic Variations in the Vitamin D Receptor Predict Type 2 Diabetes and Myocardial Infarction in a Community-Based Population: The Tromsø Study. - Ieva Martinaityte; Rolf Jorde; Henrik Schirmer; Ellisiv Bøgeberg Mathiesen; Inger Njølstad; Maja-Lisa Løchen; Tom Wilsgaard; Ragnar Martin Joakimsen; Elena Kamycheva (PLoS ONE, 2016)
[This corrects the article DOI: 10.1371/journal.pone.0145359.].